Hypoglycemic Activity of Ramulus mori Oligosaccharides on High-fat Diet/Streptozotocin-Induced Diabetic Mice - Qiaoling ZHU; Xiangyang ZHU; Shiyuan YANG; Yuxiao ZOU; Qiong YANG; Fan LIU; Erna LI (Shipin gongye ke-ji, 2023)
Ramulus mori oligosaccharides were used as the raw material to evaluate its hypoglycemic effect on high-fat diet/streptozotocin-induced diabetic mice through in vivo experiments. The diabetic mice model was established by high-fat diet combined with injection of streptozotocin, and it was given low-dose (200.00 mg/(kg·bw)), medium-dose (400.00 mg/(kg·bw)) and high-dose (800.00 mg/(kg·bw)) of Ramulus mori oligosaccharides by gavage intervention. In order to evaluate the effects of Ramulus mori oligosaccharides on biochemical indicators and intestinal flora in diabetic mice, the body weight and fasting blood glucose value of the mice were regularly measured. After 40 days, the oral glucose tolerance, insulin level, oxidative stress level, intestinal flora composition, kidney-related enzymes of the mice were measured, and the pathological morphology of the mice colon was observed. The results showed that Ramulus mori oligosaccharides alleviated the weight loss of the diabetic mice, decreased fasting blood glucose and glucose tolerance to a certain extent compared with the model group. After treatment with Ramulus mori oligosaccharides, the insulin level of diabetic mice was significantly decreased (P<0.05), the SOD and GSH activity were significantly increased (P<0.05), the MDA content was significantly decreased (P<0.05), and the CRE and BUN levels were effective reduced. By 16S rDNA analysis of the intestinal flora of the diabetic mice, it was found that Ramulus mori oligosaccharides effectively increased the abundance of intestinal microorganisms. It reduced the abundance of Firmicutes and increased the abundance of Bacteroidetes at the phylum level, increased the proportion of Lactobacillus at the family level, increased the proportion of Lactobacillus and decreases the proportion of Lachnospira at the genus level. It was confirmed that Ramulus mori oligosaccharides could reduce blood sugar, relieve weight loss in the diabetic mice, and repair colon and kidney damage by improving insulin resistance, improving oxidative stress levels, and regulating intestinal flora, thereby reducing blood glucose. It could exert a good hypoglycemic effect at a low dose (200.00 mg/(kg·bw)), but there was no obvious linear relationship between the hypoglycemic effect and the dose.